Epigenetics in non-small cell lung carcinomas - Irlanda Peralta-Arrieta; Leonel Armas-López; Joaquín Zúñiga; Federico Ávila-Moreno (Instituto Nacional de Salud Pública, 2019)
Objective. To perform a systematic review of the main epigenetic aberrations involved in non-small cell lung carcinomas' (NSCLC) diagnosis, progression, and therapeutics. Materials and methods. We performed a systematic review of the scientific literature on lung cancer epigenetics, focusing on NSCLC. Results. Several advances in the molecular study of classical epigenetic mechanisms and massive studies of lung cancer epigenome have contributed relevant new evidence revealing that various molecular complexes are functionally influencing genetic-epigenetic and transcriptional mechanisms that promote lung tumorigenesis (initiation, promotion, and progression), and are also involved in NSCLC therapy-resistance mechanisms. Conclusion. Several epigenetic complexes and mechanisms must be analyzed and considered for the design of new and efficient therapies, which could be fundamental to develop an integrated knowledge to achieve a comprehensive lung cancer personalized medicine.